Samuel Langhorne Clemens papers - Clemens, Samuel Langhorne, 1835-1910.; Twain, Mark, 1835-1910.
ALsS (1874-1901) from Clemens to various individuals, manuscript page from The Gilded Age: A Tale of Today (1874), and an autographed photograph (1908). Also includes photoreproductions of certificates, correspondence concerning Clemens (Clements) family genealogy, and printed material.
In part, positive and negative photoreproductions.
Author and humorist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Clements family; American literature; American wit and humor; Authors; Humorists